ONLINE MONITORING OF WATER RECYCLING FROM PALM OIL MILL EFFLEUENT (POME) - ABD RAHIM, MUHAMAD ARIFF BIN (Universiti Teknologi PETRONAS, 2009)
This study will demonstrate the understanding of the chosen topic, which is Online Monitoring Of Water Recycling From Palm Oil Mill Effluent (POME). The discharge of poor quality effluents by the palm oil mill is posing a serious threat to water resources. As there is very few continuous monitoring system of palm oil effluent that available so there is need to extend this to other palm oil mill. The objective of the project is to develop an online monitoring of water recycling and treatment from palm oil mill effluent. Through this study, there will be a development of online monitoring (Graphical User Interface (GUI)) using LabVIEW and Data Acquisition (DAQ) card. The parameters will be set through the software to be comparison with actual data about the quality of the water. Lab testing will be done with a model of the system for the designed system to ensure this online system will work accordingly due to desire objective.